Compliance to exercise‐oncology guidelines in prostate cancer survivors and associations with psychological distress, unmet supportive care needs, and quality of life. Issue 10 (18th June 2015) - Galvão, Daniel A.; Newton, Robert U.; Gardiner, Robert A.; Girgis, Afaf; Lepore, Stephen J.; Stiller, Anna; Mihalopolous, Cathrine; Occhipinti, Stefano; Chambers, Suzanne K.; Dunn, Jeff
Abstract Objective The purpose of this study was to determine prevalence of Australian prostate cancer survivors meeting contemporary exercise‐oncology guidelines and identify associations with distress, unmet supportive care needs, and quality of life. Methods A population‐based cohort of 463 prostate cancer survivors who were on 10.8 months post‐curative therapy was assessed for compliance with current exercise guidelines for cancer survivors, motivational readiness for physical activity, psychological distress, unmet supportive care needs, and quality of life. Results Only 57 men (12.3%) reported sufficient exercise levels (150 min of moderate intensity or 75 min of strenuous exercise per week and twice weekly resistance exercise), 186 (40.2%) were insufficiently active, and 220 (47.5%) were inactive. Among inactive men, 99 (45.0%) were in the contemplation or preparation stage of motivation readiness. Inactive men had higher global distress (p = 0.01) and Brief Symptom Inventory‐Anxiety (p < 0.05) than those who were insufficiently active. Total Supportive Care Needs and International Prostate Cancer Symptom scores were higher in inactive than insufficiently and sufficiently active men (p < 0.05). Lack of physical activity contributed to poorer quality of life. Conclusions Only a small proportion of Australian prostate cancer survivors met contemporary exercise‐oncology recommendations despite increasing recognition of exercise to improve patient outcomes. Strategies are urgently required to increase prostate cancer survivors' participation in aerobic and resistance exercise training.Copyright © 2015 John Wiley & Sons, Ltd.